Review Artikel : Aktifitas Hepatoprotektor Pada Tanaman Herbal - Hanifah, Farah; Busman, Hendri (Medula, 2024)
The liver plays a vital role in the human body, serving as a site for the metabolism of fats, carbohydrates, and proteins, as well as detoxification of toxic compounds, bile salt formation, and vascular function. Liver damage can be caused by various factors, including drugs, infections, alcohol, autoimmune disorders, or hepatitis. Substances that induce liver damage are known as hepatotoxins, commonly including NSAIDs like paracetamol and carbon tetrachloride (CCl4). Chronic hepatitis is a significant global issue, including in Indonesia, with hepatitis B and hepatitis C viruses being the most common causes. Herbal medicine is increasingly being used for health benefits worldwide, contributing significantly to human health in preventive, curative, and rehabilitative aspects. Indonesia, rich in biodiversity, presents numerous opportunities for plants with potential hepatoprotective properties. Various herbal plants containing flavonoid compounds have been found to possess anti- inflammatory and antioxidant properties. These bioactive compounds, particularly flavonoid derivatives, act as potential antioxidant prophylactic agents, crucial in protecting against liver lesions induced by CCl4. Reactive oxygen species (ROS) are believed to be responsible for the pathogenesis of various liver diseases, and studies have shown the efficacy of herbal extracts in reducing ROS levels and lipid peroxidation in ethanol-induced liver damage. Several herbal plants exhibit hepatoprotective activities, including turmeric, bee pollen honey, cinnamon, eclipta alba, Tinospora cordifolia, Mimosa pudica, and Cassia fistula L. These plants have shown effects such as antioxidant, anti-inflammatory, and antiviral properties, contributing to the protection and regeneration of liver cells, inhibition of viral replication, and modulation of immune responses. In conclusion, numerous herbal plants exhibit hepatoprotective activities through various mechanisms, including antioxidant, anti-inflammatory, antiviral, and immunomodulatory effects. Further research and exploration of these plants' therapeutic potential could lead to the development of effective treatments for liver diseases.